Benzo(a)pyrene Induced p53 Mediated Male Germ Cell Apoptosis: Synergistic Protective Effects of Curcumin and Resveratrol - Banerjee, Bhaswati; Chakraborty, Supriya; Ghosh, Debidas; Raha, Sanghamitra; Sen, Parimal C.; Jana, Kuladip (Frontiers in Pharmacology, 2016)
B(a)P (Benzo(a)pyrene) is an environmental toxicant that induces male germ cell apoptosis. Curcumin and resveratrol are phytochemicals with cytoprotective and anti-oxidative properties. At the same time resveratrol is also a natural Aryl hydrocarbon Receptor (AhR) antagonist. Our present study in isolated testicular germ cell population from adult male Wistar rats, highlighted the synergistic protective effect of curcumin and resveratrol against B(a)P induced p53 mediated germ cell apoptosis. Curcumin-resveratrol significantly prevented B(a)P induced decrease in sperm cell count and motility, as well as increased serum testosterone level. Curcumin-resveratrol co-treatment actively protected B(a)P induced testicular germ cell apoptosis. Curcumin-resveratrol co-treatment decreased the expression of pro-apoptotic proteins like cleaved caspase 3, 8 and 9, cleaved PARP, Apaf1, FasL, tBid. Curcumin-resveratrol co-treatment decreased Bax/Bcl2 ratio, mitochondria to cytosolic translocation of cytochrome c and activated the survival protein Akt. Curcumin-resveratrol decreased the expression of p53 dependent apoptotic genes like Fas, FasL, Bax, Bcl2 and Apaf1. B(a)P induced testicular ROS (Reactive Oxygen Species) generation and oxidative stress were significantly ameliorated with curcumin and resveratrol. Curcumin-resveratrol co-treatment prevented B(a)P induced nuclear translocation of AhR and CYP1A1(Cytochrome P4501A1) expression. The combinatorial treatment significantly inhibited B(a)P induced ERK 1/2, p38 MAPK and JNK 1/2 activation. B(a)P treatment increased the expression of p53 and its phosphorylation (p53 ser 15). Curcumin-resveratrol co-treatment significantly decreased p53 level and its phosphorylation (p53 ser 15). The study concludes that curcumin-resveratrol synergistically modulated MAPKs and p53, prevented oxidative stress, regulated the expression of pro and anti-apoptotic proteins as well as the proteins involved in B(a)P metabolism thus protected germ cells from B(a)P induced apoptosis.